Scabies: current knowledge and future directions - Mitchell, Elke; Wallace, Miranda; Marshall, Justine; Whitfeld, Margot; Romani, Lucia (Frontiers in Tropical Diseases, 2024)
Scabies is a global public health issue, with approximately 455 million new cases worldwide each year. Scabies is a parasitic skin disease caused by infestation with the mite Sarcoptes scabiei var. hominis that can lead to secondary skin infections such as impetigo. In 2017, scabies was added to the World Health Organization’s list of neglected tropical diseases renewing calls for effective management and control of the disease. Mass drug administration has emerged as an effective strategy to control scabies, especially in highly endemic settings. In this review, we detail scabies epidemiology and risk factors, clinical characteristics and diagnosis, as well as control options, and future areas for scabies research.